Immunoprofiling of Adult-Derived Human Liver Stem/Progenitor Cells: Impact of Hepatogenic Differentiation and Inflammation - Hoda El-Kehdy; Camillo Sargiacomo; Mohammad Fayyad-Kazan; Hussein Fayyad-Kazan; Catherine Lombard; Laurence Lagneaux; Etienne Sokal; Mehdi Najar; Mustapha Najimi (Hindawi Limited, 2017)
Adult-derived human liver stem/progenitor cells (ADHLSCs) are, nowadays, developed as therapeutic medicinal product for the treatment of liver defects. In this study, the impact of hepatogenic differentiation and inflammation priming on the ADHLSCs' immune profile was assessed in vitro and compared to that of mature hepatocytes. The constitutive immunological profile of ADHLSCs was greatly different from that of hepatocytes. Differences in the expression of the stromal markers CD90 and CD105, adhesion molecules CD44 and CD49e, immunoregulatory molecules CD73 and HO-1, and NK ligands CD112 and CD155 were noted. While they globally preserved their immunological profile in comparison to undifferentiated counterparts, differentiated ADHLSCs showed a significant downregulation of CD200 expression as in hepatocytes. This was mainly induced by signals issued from EGF and OSM. On the other hand, the impact of inflammation was quite similar for all studied cell populations with an increased expression level of CD54 and CD106 and induction of that of CD40 and CD274. In conclusion, our immune profiling study suggests CD200 as a key factor in regulating the immunobiology of differentiated ADHLSCs. A better understanding of the molecular and physiological events related to such marker could help in designing the optimal conditions for an efficient therapeutic use of ADHLSCs.